One-Year Follow-Up of Natural Killer Cell Activity in Multiple Myeloma Patients Treated With Adjuvant Lenalidomide Therapy - Besson, Laurie; Charrier, Emily; Karlin, Lionel; Allatif, Omran; Marçais, Antoine; Rouzaire, Paul; Belmont, Lucie; Attal, Michel; Lombard, Christine; Salles, Gilles; Walzer, Thierry; Viel, Sébastien (Frontiers in Immunology, 2018)
Multiple myeloma (MM) is a proliferation of tumoral plasma B cells that is still incurable. Natural Killer (NK) cells can recognize and kill MM cells in vitro, and can limit MM growth in vivo. Previous reports have shown that NK cell function is impaired during MM progression and suggested that treatment with immunomodulatory drugs (IMIDs) such as lenalidomide (LEN) could enhance it. However, the effects of IMIDs on NK cells have been tested mostly in vitro or in preclinical models and supporting evidence of their effect in vivo in patients is lacking. Here, we monitored NK cell activity in blood samples from 10 MM patients starting after frontline induction chemotherapy (CTX) consisting either of association of bortezomib-lenalidomide-Dexamethasone (VRD) or autologous Stem-cell Transplantation (SCT). We also monitored NK cell activity longitudinally each month during one year, after maintenance therapy with LEN. Following frontline chemotherapy, peripheral NK cells displayed a very immature phenotype and retained poor reactivity towards target cells ex vivo. Upon maintenance treatment with LEN, we observed a progressive normalization of NK cell maturation, likely caused by discontinuation of chemotherapy. However, LEN treatment neither activated NK cells nor improved their capacity to degranulate or to secrete IFN- or MIP1- following stimulation with MHC-I deficient or antibody-coated target cells. Upon LEN discontinuation, there was no reduction of NK cell effector function either. These results caution against the use of LEN as single therapy to improve NK cell activity in patients with cancer and call for more preclinical assessments of the potential of IMIDs in NK cell activation.